Evaluation of Some Chemical and Sensory Properties of Processed Cheese Analogue with Selected Vegetable Oils - Al-Ismail, Khalid; Al-Hiary, Bara’h; Al-Dabbas, Maher (International Journal of Chemical and Process Engineering Research, 2015)
Cheese analogues are cheese-like products with varied compositions and functional properties which produced by partial or whole replacement of milk components, in particular milk fat, by non milk-based components. The purpose of this research was to evaluate the effect of replacement of milk fat in processed cheese with different formulations from olive, corn and sesame oils on some chemical and sensory properties. The results indicated that the peroxide values were not affected by the replacement of milk fat with vegetable oils significantly (P <0.05), while the free fatty acid content was slightly but significantly affected. These two values were significant (P <0.05) increased during the three months of storage. The cholesterol contents in the cheese samples with olive, sesame and corn oils were 86.9, 84%, and 83.1%, respectively lower than those of the whole milk cheese sample. The replacement of milk fat with vegetable oils did not affect the appearance, color and tenderness of the processed cheese samples. The replacement of milk fat with vegetable oil significantly (P <0.05) affected the flavor of the cheese analogue samples.